An online tuned novel nonlinear PI controller for stiction compensation in pneumatic control valves. (September 2015) - Mishra, Puneet; Kumar, Vineet; Rana, K.P.S.
Abstract: A novel Nonlinear PI Controller (NPIC) has been proposed for effective control of flow process employing a sticky pneumatic control valve. The proposed control scheme has been inherited from a classical PI control structure with a difference that the integral gain has been varied in accordance with the instantaneous error and the rate of change of error. The tuning of controller has been carried out online using Differential Evolution algorithm. To evaluate the effectiveness of the proposed controller, a comparative study with the conventional PI controller has also been carried out for the setpoint tracking, disturbance rejection and robustness to parameter uncertainties on account of operating point change on a laboratory scale nonlinear flow process. Based on these intensive experimental evidences, it has been concluded that the NPIC performed far better than the conventional PI controller for all the case studies and suppressed effectively any stiction induced oscillations. Highlights: A novel nonlinear PI controller is designed and tested for nonlinear flow process. The proposed controller can be used standalone for effective stiction compensation. The controller was experimentally tested on a nonlinear laboratory scale flow process. The designed controller is found to be superior to conventional PI controller.